PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA SEKTOR PERBANKAN DI BEI TAHUN 2022-2024 - Fitri Utami Wayan Sari; Ika Wahyuni; Lita Permata Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
The capital market serves as in investment medium utilized by investors to allocate capital with the expectation of generating future returns. In making investment decisions, investors generally consider various factors capable of influencing a company’s stock price, including capital structure, firm size, profitability, and the implemented dividend policy. This study aims to analyze the effect of capital structure, firm size, and profitability on stock prices with dividend policy serving as an intervening variable in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research employs a quantitative approach using data obtained from companies’ financial statements. The population consists of banking sector companies listed on the Indonesia Stock Exchange, with a sample of 15 companies selected through a purposive sampling technique. Data were analyzed using the Structural Equation Modeling-partial Least Square (PLS-SEM) method, with the assistance of SmartPLS 3.0. software. The results indicate that capital structure and profitability have a positive and significant effect on dividend policy, while firm size has a negative and significant effect on dividen policy. Regarding stock prices, firm size and profitability have a positive and significant effect, whereas capital structure has an negative but insignificant effect. Furthermore, dividend policy has a positive but insignificant effect on stock prices. The indirect effect analysis reveals that dividend policy is unable to mediate the effects of capital structure, firm size, and profitability on stock prices.